Biomedical engineering II : recent developments : proceedings of the Second Southern Biomedical Engineering Conference (Pergamon Press, 1983)
Biomedical Engineering II: Recent Developments covers some progress made in biochemical engineering, which have some useful application in dentistry, medical instrumentation, and orthopedics. The book provides a detailed testing and analysis of the use of hydroxylapatite as an effective substance for mandibular augmentation of the atrophic ridge. An in-depth report about the technique called the tendon reroute surgery is also given.